Lateralized brain connectivity in auditory verbal hallucinations: fMRI insights into the superior and middle temporal gyri - Zaykova, Vyara; Kandilarova, Sevdalina; Paunova, Rositsa; Popova, Ferihan; Stoyanov, Drozdstoy (Frontiers in Human Neuroscience, 2025)
IntroductionAuditory verbal hallucinations are one of the most prevalent positive symptoms associated with schizophrenia. The superior and middle temporal gyri have been demonstrated to play a role in auditory and language perception. Dysfunction in the temporal cortex has been associated with the development of psychosis. The aim of the present study was to explore the functional connectivity and laterality of superior and middle temporal gyri in patients with auditory verbal hallucinations.MethodsResting-state functional magnetic resonance imaging data was obtained from a total of 105 subjects including 63 healthy controls and 42 patients diagnosed with schizophrenia experiencing auditory verbal hallucinations. A comparative analysis was conducted to assess the functional connectivity of the superior and middle temporal gyri bilaterally.ResultsThe comparison between the two groups revealed several significant differences in the resting-state functional connectivity of the superior and middle temporal gyri in patients with auditory verbal hallucinations as compared to healthy controls. The aberrant connections were focused on the anterior part of the right superior temporal gyrus and the posterior part of the left one, as well as in the posterior division of the right middle temporal gyrus and both anterior and posterior divisions of the left middle temporal gyrus.DiscussionThe observed dysconnectivity between the named subdivisions of the temporal lobe and cortical and subcortical structures suggests that the aberrant connectivity and brain lateralization may be related to the etiopathogenesis of schizophrenia and auditory verbal hallucinations.